2023
DOI: 10.1177/00469580231160888
|View full text |Cite
|
Sign up to set email alerts
|

Community Nurses Are Important Providers of Continuity of Care for Patients With Chronic Diseases: A Qualitative Study

Abstract: To clarify the functional orientation of community health nurses in the continuous care of patients with chronic diseases and to encourage community nurses to play their expected roles in extended nursing work. In this study, conducted from May to July 2020, the staff of Shanghai Community Health Service Center were sampled, and representative medical staff were selected for in-depth interviews and focus group discussions. Eighteen community medical staff members participated. The functions of community nurses… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 6 publications
(5 reference statements)
1
4
0
Order By: Relevance
“…Similarly, the findings in this thesis indicate that a consistent presence of NPs in municipal healthcare setting can help mitigate care-related injuries and reduce hospital admissions (II-III). The importance of maintaining high levels of continuity aligns with studies conducted by Ge et al (2023) and Lowe et al (2022), both of which confirmed the significance of such continuity for older adults with complex care needs. Specifically, Lowe et al (2022) found that the substantial continuity provided by NPs led to a 51% reduction in hospitalization.…”
Section: Nps' Expanded Practice Enhancing Personcentred Care and Prov...supporting
confidence: 67%
“…Similarly, the findings in this thesis indicate that a consistent presence of NPs in municipal healthcare setting can help mitigate care-related injuries and reduce hospital admissions (II-III). The importance of maintaining high levels of continuity aligns with studies conducted by Ge et al (2023) and Lowe et al (2022), both of which confirmed the significance of such continuity for older adults with complex care needs. Specifically, Lowe et al (2022) found that the substantial continuity provided by NPs led to a 51% reduction in hospitalization.…”
Section: Nps' Expanded Practice Enhancing Personcentred Care and Prov...supporting
confidence: 67%
“…According to previous reports, 11 home-based patients with chronic diseases, such as disabled individuals, dementia patients, and disabled elderly individuals, and their caregivers hope that their treatment plans formulated by higher-level hospitals can be continued in the community or at home. Community nurses should provide home-based patients with convenient, standardized and safe care so that they can enjoy the same care as patients in higher-level hospitals.…”
Section: Discussionmentioning
confidence: 99%
“…On the basis of the findings of a previous qualitative study, 11 the Beredi comparative study method was used. The role model indices and corresponding dimension settings of 3 representative community nurses were described, explained and compared, and representative indicators were selected to form a framework.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…The role of community nursing interventions has become increasingly important, in tackling this problem. 1,2 These interventions provide strategies to enhance the well-being and quality of life for individuals who are dealing with conditions. This review explores aspects of community nursing interventions in managing diseases, focusing on their effectiveness, challenges, and areas that can be improved upon.…”
mentioning
confidence: 99%